At the crossroads of fertility and metabolism: the importance of AMPK-dependent signaling in female infertility associated with hyperandrogenism. Issue 6 (23rd April 2022) - Froment, Pascal; Plotton, Ingrid; Giulivi, Cecilia; Fabre, Stephane; Khoueiry, Rita; Mourad, Nizar I; Horman, Sandrine; Ramé, Christelle; Rouillon, Charlène; Grandhaye, Jeremy; Bigot, Yves; Chevaleyre, Claire; et al.
Abstract: STUDY QUESTION: What biological processes are linked to the signaling of the energy sensor 5′-AMP-activated protein kinase (AMPK) in mouse and human granulosa cells (GCs)? SUMMARY ANSWER: The lack of α1AMPK in GCs impacted cell cycle, adhesion, lipid metabolism and induced a hyperandrogenic response. WHAT IS KNOWN ALREADY: AMPK is expressed in the ovarian follicle, and its activation by pharmacological medications, such as metformin, inhibits the production of steroids. Polycystic ovary syndrome (PCOS) is responsible for infertility in approximately 5–20% of women of childbearing age and possible treatments include reducing body weight, improving lifestyle and the administration of a combination of drugs to improve insulin resistance, such as metformin. STUDY DESIGN, SIZE, DURATION: AMPK signaling was evaluated by analyzing differential gene expression in immortalized human granulosa cells (KGNs) with and without silencing α1AMPK using CRISPR/Cas9. In vivo studies included the use of a α1AMPK knock-out mouse model to evaluate the role of α1AMPK in folliculogenesis and fertility. Expression of α1AMPK was evaluated in primary human granulosa-luteal cells retrieved from women undergoing IVF with and without a lean PCOS phenotype (i.e. BMI: 18–25 kg/m 2 ). PARTICIPANTS/MATERIALS, SETTING, METHODS: α1AMPK was disrupted in KGN cells and a transgenic mouse model. Cell viability, proliferation and metabolism were evaluated. Androgen production was evaluated by analyzing protein levels of relevant enzymes in the steroid pathway by western blots, and steroid levels obtained from in vitro and in vivo models by mass spectrometry. Differential gene expression in human GC was obtained by RNA sequencing. Analysis of in vivo murine folliculogenesis was performed by histology and immunochemistry, including evaluation of the anti-Müllerian hormone (AMH) marker. The α1AMPK gene expression was evaluated by quantitative RT-PCR in primary GCs obtained from women with the lean PCOS phenotype (n = 8) and without PCOS (n = 9). MAIN RESULTS AND THE ROLE OF CHANCE: Silencing of α1AMPK in KGN increased cell proliferation ( P < 0.05 versus control, n = 4), promoted the use of fatty acids over glucose, and induced a hyperandrogenic response resulting from upregulation of two of the enzymes involved in steroid production, namely 3β-hydroxysteroid dehydrogenase (3βHSD) and P450 side-chain cleavage enzyme (P450scc) ( P < 0.05, n = 3). Female mice deficient in α1AMPK had a 30% decrease in their ovulation rate ( P < 0.05, n = 7) and litter size, a hyperandrogenic response ( P < 0.05, n = 7) with higher levels of 3βHSD and p450scc levels in the ovaries, and an increase in the population of antral follicles ( P < 0.01, n = 10) compared to controls. Primary GCs from lean women with PCOS had lower α1AMPK mRNA expression levels than the control group ( P < 0.05, n = 8–9) LARGE SCALE DATA: The FastQ files and metadata were submitted to the European Nucleotide Archive (ENA) at EMBL-EBI under accession number PRJEB46048. LIMITATIONS, REASONS FOR CAUTION: The human KGN is a not fully differentiated, transformed cell line. As such, to confirm the role of AMPK in GC and the PCOS phenotype, this model was compared to two others: an α1AMPK transgenic mouse model and primary differentiated granulosa-lutein cells from non-obese women undergoing IVF (with and without PCOS). A clear limitation is the small number of patients with PCOS utilized in this study and that the collection of human GCs was performed after hormonal stimulation. WIDER IMPLICATIONS OF THE FINDINGS: Our results reveal that AMPK is directly involved in steroid production in human GCs. In addition, AMPK signaling was associated with other processes frequently reported as dysfunctional in PCOS models, such as cell adhesion, lipid metabolism and inflammation. Silencing of α1AMPK in KGN promoted folliculogenesis, with increases in AMH. Evaluating the expression of the α1AMPK subunit could be considered as a marker of interest in infertility cases related to hormonal imbalances and metabolic disorders, including PCOS. STUDY FUNDING/COMPETING INTEREST(S): This study was financially supported by the Institut National de la Recherche Agronomique (INRA) and the national programme « FERTiNERGY » funded by the French National Research Agency (ANR). The authors report no intellectual or financial conflicts of interest related to this work. R.K. is identified as personnel of the International Agency for Research on Cancer/World Health Organization. R.K. alone is responsible for the views expressed in this article and she does not necessarily represent the decisions, policy or views of the International Agency for Research on Cancer/World Health Organization. TRIAL REGISTRATION NUMBER: N/A.